Annual report 2006. - Asia United Bank (Pasig City Asia United Bank, 2006)
AUB provides, directly and through its subsidiaries, a wide range of banking and other financial products and services, including corporate and consumer loans, deposit products, corporate banking, treasury and trust products, cash management solutions, and other services. Such products are offered to a wide range of customers, including consumers, SMEs and large corporations.
Keywords: Bank correspondence; Bank sector